(untitled) (Tokyo, Japan, 2020)
In this book, the authors analyze the present conditions of the alliance and discuss its future direction from this perspective of maintaining the maritime security order in the Asia-Pacific region. Together with the diplomatic and security policies of Japan and the US, and of China, their research subjects include the policies of India, Australia, South Korea, Russia, and ASEAN, which are the main players in the oceans of the region, and they derive important hints for the future of the Japan-US alliance.
Keywords: Nhật Bản,Japan; Ngoại giao,Foreign relations; Hoa Kỳ,United States